Effect of Combined Application of Calcium and Zinc on Fruit Quality of Tomato - WANG Fei, ZHOU Weitong, Liang Liting, ZHANG Chengfeng, YANG Xiaohui, ZHANG Yi, HOU Leiping, SHI Yu (Shipin Kexue)
In this study, the effect of basal zinc fertilization combined with foliar application of calcium on the appearance, nutritional and flavor quality of tomato (cv. Zheyingfen 1) was investigated through pot cultivation experiments. Basal zinc fertilization at two concentrations (0 and 0.1 g/L) followed by foliar application of different concentrations of CaCl2 (0, 2.5, 5, and 10 g/L) was performed in a total of 8 treatments. The results showed that the combined application of calcium and zinc significantly improved the appearance of tomato fruit and increased the number of fruits per cluster, fruit transverse diameter, and single fruit mass, the most pronounce effect being observed in the 0.1 g/L zinc + 5 g/L CaCl2 treatment (T6). In terms of nutritional quality, the combined application significantly enhanced the contents of soluble solids, soluble protein, vitamin C, lycopene, and flavonoids in tomato fruit, with the most pronounced effect being observed in treatment T6. The combined application of calcium and zinc also significantly influenced the composition and content of amino acids in tomato fruit. The contents of various taste-active amino acids and essential amino acids were the highest in treatment T6, showing that this treatment improved the flavor quality of tomatoes. Additionally, the combined application significantly affected the types and contents of volatile flavor compounds in tomato fruit, increasing the levels of substances that contribute positively to tomato flavor. Principal component analysis (PCA) showed that treatment 6 gained the highest comprehensive score. In conclusion, compared with individual applications, the combined application of calcium and zinc more effectively promoted fruit growth and development, enhanced overall nutritional quality, and facilitated the accumulation of flavor compounds. The combination of 0.1 g/L zinc and 5 g/L calcium chloride demonstrated the best promoting effect on tomato fruit quality.